The Effect of Motivation, Job Satisfaction, Organizational Culture and Work Environment on Organizational Commitment to Employees: Pengaruh Motivasi, Kepuasan Kerja, Budaya Organisasi dan Lingkungan Kerja Terhadap Komitmen Organisasi Pada Karyawan - Heriyanto, Muhammad Ferdiawan; Rizal, Asat (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of motivation, job satisfaction, organizational culture, and work environment on organizational commitment to employees of PT. Jasa Marga Pandaan-Malang. This study uses quantitative methods. The type of research used is descriptive research. The population in this study were all employees of PT. Jasa Marga Pandaan-Malang, which has 96 employees. Sampling using the